Sleep Study and Oximetry Parameters for Predicting Postoperative Complications in Patients With OSA - Suen, Colin (Chest, 2019)
In the surgical setting, OSA is associated with an increased risk of postoperative complications. At present, risk stratification using OSA-associated parameters derived from polysomnography (PSG) or overnight oximetry to predict postoperative complications has not been established. The objective of this narrative review is to evaluate the literature to determine the association between parameters extracted from in-laboratory PSG, portable PSG, or overnight oximetry and postoperative adverse events. We obtained pertinent articles from Ovid MEDLINE, Ovid MEDLINE In-Process & Other Non-Indexed Citations, and Embase (2008 to December 2017). The search included studies with adult patients undergoing surgery who had OSA diagnosed with portable PSG, in-laboratory PSG, or overnight oximetry that reported on specific sleep parameters and at least one adverse outcome. The search was restricted to English-language articles. The search yielded 1,810 articles, of which 21 were included in the review. Preoperative apnea-hypopnea index (AHI) and measurements of nocturnal hypoxemia such as oxygen desaturation index (ODI), cumulative sleep time percentage with oxyhemoglobin saturation (Spo(2)) < 90% (CT90), minimum Spo(2), mean Spo(2), and longest apnea duration were associated with postoperative complications. OSA is associated with postoperative complications in the population undergoing surgery. Clinically and statistically significant associations between AHI and postoperative adverse events exists. Complications may be more likely to occur in the category of moderate to severe OSA (AHI ≥ 15). Other parameters from PSG or overnight oximetry such as ODI, CT90, mean and minimal Spo(2), and longest apnea duration can be associated with postoperative complications and may provide additional value in risk stratification and minimization.